Background Paper: 2nd Functional Exercise of the MOSPA Agreement - Emergency Prevention, Preparedness, and Response (EPPR) (Emergency Prevention, Preparedness, and Response (EPPR), 2016)
"2016 EPPR MOSPA Agreement Exercise: In December 2015, representatives of the EPPR exercise design team met in Reykjavik, Iceland where the objectives and scenario for the June 2016 EPPR MOSPA Agreement table-top exercise were presented and approved by EPPR. By utilizing a tanker collision scenario based in Norway, EPPR will be able to further test the updated notification protocols, increase complexity of international request-for-support activities, and incorporate use of a common operating picture platform that can be shared across the Arctic states. The three stage exercise will begin with a standard notification with requests for assistance, followed by each state analyzing their internal protocols for offering assistance. Finally, in June 2016, the EPPR exercise design team will meet on the margins of the 2016 EPPR I meeting to discuss the results of the request and offers of assistance, as well as each state’s internal protocols for providing such assistance."